CRISPR/Cas9 and Nanotechnology Pertinence in Agricultural Crop Refinement - Naik, Banavath Jayanna; Shimoga, Ganesh; Kim, Seong-Cheol; Manjulatha, Mekapogu; Subramanyam Reddy, Chinreddy; Palem, Ramasubba Reddy; Kumar, Manu; Kim, Sang-Youn; Lee, Soo-Hong (Frontiers in Plant Science, 2022)
The CRISPR/Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated protein 9) technology is a versatile technique that can be applied in crop refinement technology. Currently, the main reasons for declining agricultural yield are global warming, low rainfall, biotic and abiotic stresses, as well as reduced soil fertility caused by use of harmful chemicals. These declining yields lead to inadequate global food production and numerous other issues. Grains and horticultural crops including fruits, vegetables, and ornamental plants are crucial in sustaining human life. Genomic editing using CRISPR/Cas9 technology has numerous advantages in crop development. Improving crop production using transgenic-free CRISPR/Cas9 technology is essential to overcome the universal food scarcity caused by rapidly increasing global demand. The present review discusses on the potential applications of CRISPR/Cas9 technology in developing of the cultivation of major agricultural crops. In addition to their applications in gene- edited crops thus far, the limitations and major challenges of genome editing in grains, vegetables, and fruits have been discussed here as well as the applications of nanoparticles (NPs) in crop improvement.